MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA DENGAN MENGGUNAKAN METODE DEMONSTRASI PADA SISWA KELAS IV SD NEGERI 162091 KOTA TEBING TINGGI - Sariannauli Purba (ELEMENTARY SCHOOL JOURNAL PGSD FIP UNIMED, 2017)
This study aims to improve students' learning outcomes in Mathematics subjects through Demonstration methods. The method of this research is classroom action research (PTK). Learning by demonstration method in Mathematics lesson in Grade IV of SD Negeri 162091 Kota Tebing Tinggi has a positive impact in improving students 'interest and achievement which is marked by improvement of students' learning mastery in every cycle, that is pre cycle average 58,43, cycle I 67.81, cycle 2 83.12 and declared successful classically with an average of 83.12. Keywords: Demonstration, Learning Outcomes, Mathematics